Feasibility Study Aireon Space Based ADS-B in Indonesia - Jaya, Taruna; Hartono, Lukie; Fatonah, Feti; Mukti, Indra Fadillah; Aritama, Dewa Putu Kidang (Peneliti.net, 2024)
Space Based ADS-B technology is the latest technology from the development of conventional ADS-B which still uses a ground station. This technology is a system formed by satellites that are connected to each other as receivers of broadcast data from aircraft so that they can provide a wider level of surveillance in global airspace. This research aims to determine the extent of the implementation of Space Based ADS-B in Indonesia, including collaborating and comparing ADS-B data in oceanic areas and specific areas whose coverage is difficult to reach by ADS-B ground stations. This research uses a simulation-based analysis method using the Radar Analysis Support Systems for Real Time (RASS-R) application and the Radar Site Modeling (RSM) application and analyzes the comparison of the availability of ADS-B ground station and ADS-B space-based data. The results of this research show that the availability of data from space-based ADS-B can cover all regions of Indonesia